PENGARUH PARTISIPASI MASYARAKAT, KOMPETENSI SUMBER DAYA MANUSIA, DAN PENGAWASAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI KASUS PADA KABUPATEN ACEH BARAT DAYA) - Siti Umaira; Adnan Adnan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this study is to examine the effects of community participation, human resource competence, and supervision on accountability of village fund management (a case study in Kabupaten Aceh Barat Daya). This is a quantitative study with questionnaire used as the primary data elicitation and Likert scale as the measure. The study was carried out in Kabupaten Aceh Barat Daya. A total of 120 respondents were selected, consisting of the villages’ tuha peut and public figures. The simple random sampling was used as the sampling technique with the Slovin formula for determining the number of samples. The multiple linear regression was employed as the data analysis technique, facilitated by the SPSS version 21. The results indicate that the public participation (X1), human resource competency (X2), and supervision (X3) variables either partially or simultaneously have significant effects on the accountability of village fund management (Y).